Medicine meets virtual reality 20: NextMed/MMVR20 ; [the proceedings of the 20th NextMed/MMVR Conference, held in San Diego, California, USA, in February 2013] - Westwood, James D.; Westwood, S.W.; Felländer-Tsai, L. (Studies in health technology and informatics, 2013)
Since 1992, when it began as the ""Medicine Meets Virtual Reality"" conference, NextMed/MMVR has been a forum for researchers utilizing IT advances to improve diagnosis and therapy, medical education, and procedural training. Scientists and engineers, physicians and other care providers, educators and students, military medicine specialists, futurists, and industry: all come together with the shared goal of making healthcare more precise and effective. This book presents the proceedings of the 20th NextMed/MMVR conference, held in San Diego, California, USA, in February 2013. It covers a wide
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2013 -- San Diego